Josephus’s Knowledge of Scripture - Satlow, Michael L. (Journal of ancient Judaism, 2020)
Abstract Scholars have long debated whether Josephus learned Scripture while he was in Jerusalem or only once he got to Rome. The question intersects with, and is hard to answer without, a more general assessment of language use and the education of the (priestly) elite in Jerusalem at that time. This paper argues that Josephus knew little Hebrew and never learned to read Scripture in the original; he was, in this respect, typical of the Jewish elite. His introduction to written Scripture was in its Greek translation, in Rome.